PERANCANGAN SISTEM INFORMASI GPS TRACKING KENDARAAN BERBASIS WEB PADA PT BINTANG KARYA PERDANA JAKARTA - Yasin, Muhammad; Nasril, Nasril; Syamsurizal, Syamsurizal (JURNAL LENTERA ICT, 2020)
PT Bintang Karya Perdana is a company engaged in contractors, general suppliers, and information technology. To develop wings in the field of information technology. PT Bintang Karya Perdana specializes in providing GPS tracking services. Equipped with a VTS system (Vehicle Tracking System) and a vehicle control system. PT Bintang Karya Perdana is located at Jl. Al-Ridwan Mosque No. 39D, Jati Padang, South Jakarta. In running the system VTS and vehicle control systems at PT Bintang Karya Perdana are still very simple and too complicated to use this VTS system. Moreover, in making reports, tracking data still has to be manually inputted into excel or similar applications from data that can only be seen on the VTS default system. Keywords: Information System, GPS Tracking.